Evaluation of Problem Based Learning Implementation in Vocational Schools - Mulyadi Mulyadi; A. Erni Ratna Dewi; Supriadi Supriadi (Journal of Pedagogi, 2025)
The implementation of Problem-Based Learning (PBL) in vocational schools is an innovative strategy to improve student competence in accordance with industry demands. PBL places students as active subjects in the learning process, encouraging the development of critical thinking, problem-solving, and teamwork skills. However, its success faces challenges such as the readiness of teaching staff as facilitators, limited facilities and infrastructure, and the alignment of problem design with industry needs. Some vocational schools still have difficulty adapting this method due to the lack of training for teachers and limited resources to support project-based learning. In addition, the lack of industry involvement in curriculum design causes learning materials to be less relevant to the world of work. Therefore, close collaboration between schools and industry is needed to ensure that PBL can reflect the real challenges faced in the world of work. Strategic partnerships and the use of cloud-based technology can be a solution in overcoming facility constraints. Periodic evaluations of the implementation of PBL are also needed to measure its effectiveness in improving graduates' job readiness. With the right approach, PBL has the potential to become a superior method in producing an adaptive, competent, and ready workforce to face modern industrial dynamics